KEKUATAN LATERAL SAMBUNGAN KAYU MAHONI DENGAN PASAK KAYU WALIKUKUN DAN PEREKAT POLYMER ISOCYANATE - , khukuh franjaya, Ali Awaludin, ST.,M.Eng., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Utilization of wood material as element of structure had been applied in many building, house, bridge application and any else. The strenght of structures themselves were be more influenced by connection configuration in addition to its material behaviour. Availability of connenctor were made in metal such as iron and steel can be able to find them in many market. Unfortunatelly, they were produced by non-renewable resources. Hence, another option need to be found for economic and efficency consideration such as wood dowel and adhesive. This research aims to find the effect of dowel diameter into strength of wood connection. In other hand this research investigated the comparation results of Mahoniâs and Walikukunâs dowel on to analysis of lateral resistance theory (European Yield Model, EYM) then to find out failure mechanism of three types of the wood connection systems. In this research, Walikukun were used in dowel in 12 mm and 16 mm diameter and 300 mm for its length. Mahoni were used in wood material were connected with 35 mm and 40 mm for its thickness. The adhessive material were used in this research are PI 120 and PI 3200. Wood connection system with dowel in 12 mm for its diameter has the highest strength is in 25,52 kN, and the lowest one is 15,32 kN. While in 16 mm diameter has a connection strength in average 2,10 kN (9,34%) larger then 12 mm diameter of dowel system. The comparation of lateral resistancy wood experimentally on EYM theory is about Â± 11,40%. The mode of wood connection in dowel systems shows that any deterioration in the connector. While in the adhessive system connector shows that shear failure in the wood fibre. Generally, all failure mode of both connection systems were dominated proceeded by shear failured of adhessive than wood dowel systems failure. A many of lateral resistancy wood experimentally can be result a empirical comparison to calculated of lateral resistancy wood is Z = (Ï x Ao) +(0,4xY)+2,21. The utilization wood connection with wood dowel system and adhessive connection combination can be applied in building structure component e.g: truss system. Key words: connection, wood, wood dowel, adhesive